Tradisi Pembacaan Al-Qur’an di Sebuah Keluarga di Kediri, Jawa Timur - Lailatunnadhiroh; Adrika Aini (Tebuireng: Journal of Islamic Studies and Society, 2022)
Living Quran is a study of phenomena that exist in the midst of people who are living the text of the Koran by accepting, responding, utilizing or using it in their daily lives. This paper aims to describe the meaning contained in the tradition of Reading Selected Letters in the Family of Mr. Khalimi Kras Kediri. This paper uses an ethnographic approach through living Quran research accompanied by qualitative descriptive methods, also focuses on the sociological theory offered by Karl Mannheim with a sociological analysis of knowledge. The results of the research with this analysis found that the meaning of the tradition of reading the reading of Surat al-Ikhlas, Surah al-Falaq, Surah an-Nas, Ayat Kursi and Surah at-Taubah verses 128-129 after fardhu prayers are: Objective meaning, this tradition becomes a habit that can be istiqomah to be implemented. Expressive meaning, from this tradition is understood as a manifestation of the dhikr to Allah swt to achieve security and sufficiency. Documentary meaning, actors are not fully aware that what they have done in the tradition is part of the meaning of reviving the Qur'an in the family environment.